Military men as writers - Nichols, Harriet Grace (My University, 1898)
Introduction: The idea of literary work of any kind is not usually associated with the popular conception of a military man, and probably with reason, for we find, upon investigation, that men in the army are not, as a rule, writers. As one authority expresses it, “The military pen is generally no more flexible than a sponge staff.” Why is it? Is it because they are uneducated? Is it true, as Gen. Cullum asserts that “to find a scholar among military men is for the unexpected to happen?” Mountaigne too, says that the most warlike nations are the most ignorant, citing the Turks, and Goths; that Rome was more valiant before she grew so learned, - but does it necessarily follow that it was because of her increased knowledge that she became less valiant? Study the history of Rome and you will find that he decline and downfall was not due to increased intelligence and learning but to far different causes. As to the Goths and Turks, they are not to be classed with civilized nations. They are barbarians, in war, as in peace. Finally, are military men so important?
Citation: Nichols, Harriet Grace. Military men as writers. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Literary; Rome; Military Men; Scholar; Writer; Theses; Manuscripts (documents)